Correlation between Anti cyclic-citrullinated-‎eptide and rheumatoid Factor Antibodies ‎‎“levels in” Patients with from Rheumatoid ‎Arthritis (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
To  identify  diagnostic   utilities  of   Anti   citrullinated   protein   (ACCP)   and Rheumatoid   factor  (RF)   are  autoantibodies (Abs  directly  against an self-individual antigens),  Analytical  study.  The  questioner  reported  for  50  patients  with  RA were collected  from  Department  of  Rheumatology¸  AL˗Sader  Teaching  Hospital.  Serum levels  of  RF & (ACCP)  Abs  were  determinated  by enzyme ˗ linked immunosorbent assay”, while  the  level  of  erythrocyte  sedimentation  rate  (ESR)  was determined by westergreen  method.   Distribution  of  RA occur  in  females  more  than  males which  reached  (80%)  &  (20%)  respectively  according  to  the  patients group. The patients divided  according  to the  age  into  three  groups (50). The  percent for  these  groups  were  (16%)¸ (52%) & (32%). Among the 50 patients with RA¸ CCP and  ESR  49  patients  (98%)  tested  positive  for  (ACCP)  antibodies¸ and 22 patients (44%)  tested  positive for RF. and 37  patients(74% ) tested increasing levels of ESR in RA  patients. The  mean  value of (ACCP) & ESR shows highly significance  (P